The Effectiveness Of Collaborative Writing Of Narrative Essays Among Malaysian Lower Secondary School Students - Muniswaran, Jeya Chitrah (2020)
The traditional writing instruction (TWI) and the collaborative writing technique (CWT) were employed in this quasi-experimental study, which involved a total of 125 lower secondary students from two schools in Malaysia. One school used the TWI while the other school used the CWT. Data collection was over a period of five months. The research focus was to explore the effectiveness of the CWT in enhancing students’ writing performance in narrative essays. The CWT is a learner centred instruction that encompasses the development of multiple skills as students mentally, physically, socially and emotionally engage in the writing task